Metafísica y Matemáticas - Moreno Dávila, Julio (Alpha Omega, 2014)
Summary: This essay defends the thesis that mathematics reduces the number of Aristotelian categories to two: substance and relation. This leads the author to defend mathematics against what, for him, is the unjust accusation that it is the science of one of the less important Aristo-telian categories: quantity. To apply mathematics to some particular area is to study the aforementioned categories, essence and relation, within that area. Sommario: Questo piccolo lavoro propone la tesi secondo cui la matematica riduce le dieci categorie aristoteliche a due soltanto: sostanza y relazione. Inoltre, l’Author difende questa disciplina dall’accusa (ingiusta secondo lui) di ocuparsi soltanto della quantità, una delle meno importanti categorie aristoteliche dell’essere. Applicare la matematica a qualche area particolare sarebbe invece studiare le categorie di cui sopra, l’essenza e la relazione, all’interno di tale area. Key Words: mathematics, essence, relation, quantity, Aristotelian categories. Parole chiave: matematica, sostanza, relazione, quantità, categorie aristoteliche.